Psychological Features of Maladjusted Adolescents’ Behavioural Manifestations - Semencha, L. G. (Psychological Prospects Journal, 2012)
Such terms as «adjustment», «unadjustment», «disadaptation», «maladjustment» and «intractability» were analyzed in different scientific conceptions of this article. The results’ interpretation of the research about maladjusted adolescents’ dominant syndromes, disadaptation’s index, social-psychological adaptation’s (disadaptation’s) level and distinctive characteristics of their influence on the teenage pupils’ behaviour were pointed out.